Alginate-Dependent Gene Expression Mechanism in Sphingomonas sp. Strain A1 - Hayashi, Chie (American Society for Microbiology, 2014)
Sphingomonas sp. strain A1, a Gram-negative bacterium, directly incorporates alginate polysaccharide into the cytoplasm through a periplasmic alginate-binding protein-dependent ATP-binding cassette transporter. The polysaccharide is degraded to monosaccharides via the formation of oligosaccharides by endo- and exotype alginate lyases. The strain A1 proteins for alginate uptake and degradation are encoded in both strands of a genetic cluster in the bacterial genome and inducibly expressed in the presence of alginate. Here we show the function of the alginate-dependent transcription factor AlgO and its mode of action on the genetic cluster and alginate oligosaccharides. A putative gene within the genetic cluster seems to encode a transcription factor-like protein (AlgO). Mutant strain A1 (ΔAlgO mutant) cells with a disrupted algO gene constitutively produced alginate-related proteins. DNA microarray analysis indicated that wild-type cells inducibly transcribed the genetic cluster only in the presence of alginate, while ΔAlgO mutant cells constitutively expressed the genetic cluster. A gel mobility shift assay showed that AlgO binds to the specific intergenic region between algO and algS (algO-algS). Binding of AlgO to the algO-algS intergenic region diminished with increasing alginate oligosaccharides. These results demonstrated a novel alginate-dependent gene expression mechanism. In the absence of alginate, AlgO binds to the algO-algS intergenic region and represses the expression of both strands of the genetic cluster, while in the presence of alginate, AlgO dissociates from the algO-algS intergenic region via binding to alginate oligosaccharides produced through the lyase reaction and subsequently initiates transcription of the genetic cluster. This is the first report on the mechanism by which alginate regulates the expression of the gene cluster.